Pengaruh Pemasaran Relasional dan Kepuasan Nasabah terhadap Loyalitas Nasabah: Studi Kasus AJB Bumiputera 1912 Kantor Wilayah Medan - Amelia, Anjani Rizky; Nurbaiti; Aslami, Nuri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine whether or not there is influence of relational marketing and customer satisfaction on customer loyalty at the company AJB BUMIPUTERA 1912 Medan regional office. The methodology used in this study is a quantitative method with an associative approach. The variables in this study are relational marketing and customer satisfaction as independent variables and customer loyalty as the dependent variable. Samples were taken from AJB BUMIPUTERA 1912 customers in the Medan regional office, totaling 95 people. The type of data used is primary data. The data analysis method used is Instrument Test, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test. Based on the results of the adjusted R value obtained from the SPSS processing is 0.825 which means that relational marketing and customer satisfaction can explain the customer loyalty variable of 82.5% and the remaining 17.5% is explained by other variables not examined in this study. Based on the results of the F test analysis, it is known that the value of fcount (222.202) > ftable (3.10) and sig (0.000) < α (0.05). This means proving that relational marketing and customer satisfaction simultaneously have a positive and significant effect on customer loyalty. Keywords : customer satisfaction, customer loyalty, relational marketing.